Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/978-81-322-2355-9_3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Yield Strength, Pre-strain, and Curvature on Stiffness and Static Dent Resistance of Formed Panel

Abstract: Increased importance on weight reduction is driving automotive industries to reduce thickness of the steel panels without compromising the vehicle safety and performance. High strength steels are looked at as a candidate for automotive applications. To overcome the limitation of less formability in high strength steel, steel makers introduced the bake hardening steel (BH) grades. This study compares the formability of extra deep draw (EDD) steel grades which are mainly used for body panels with that of bake ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 8 publications
(6 reference statements)
0
7
2
Order By: Relevance
“…Furthermore, low yield strength also makes EDD steel susceptible to denting. 13 Due to these properties, which are unique for a steel alloy, EDD steel is extensively used for non-structural components 14 and preferred by the automobile industry for making bodyin-white components, door inners, dash panels, bodyside inners, and floor pans with spare tire tub. 15,16 To extend the benefits of ISF to the automotive industry, it is important to gauge the scope of ISF and its limitations while forming components out of EDD steel sheets.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, low yield strength also makes EDD steel susceptible to denting. 13 Due to these properties, which are unique for a steel alloy, EDD steel is extensively used for non-structural components 14 and preferred by the automobile industry for making bodyin-white components, door inners, dash panels, bodyside inners, and floor pans with spare tire tub. 15,16 To extend the benefits of ISF to the automotive industry, it is important to gauge the scope of ISF and its limitations while forming components out of EDD steel sheets.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of FLC of BH steel estimated experimentally in the present study with (a) experimental data reported in literature 1,3 as well as (b) numerically estimated using Keeler and Brazier 27 and Paul 28 models.…”
Section: Resultsmentioning
confidence: 71%
“…In recent years, one of the major emphases of automobile industries is to use thinner gauge steel sheets to improve environmental performance by reducing fuel consumption and greenhouse gas emissions without compromising passenger safety. 13 The use of thinner gauge steel sheets necessitates a favorable combination of desired properties, including high tensile strength and ductility, good surface finish, dent resistance, and good formability. 4 However, these requirements are often contradictory as it is difficult to achieve high strength without compromising formability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations